Comparative Analysis of NIST SP 800-86 Framework in Handling Digital Evidence in Cloud Computing Environment - Anton Maulana Ibrahim; Mirza Sutrisno; Asrudin (Journal of Nexural Intelligence, 2026)
This study analyzes the effectiveness of NIST SP 800-86 in handling digital evidence within cloud computing environments in Indonesia, employing a mixed-methods sequential explanatory approach. The research methods comprised a systematic literature review (SLR) of 120 publications, an implementation readiness survey (n = 110), in-depth interviews with 12 subject-matter experts, and a five-dimensional gap analysis. Findings indicate that NIST SP 800-86 exhibits an average coverage gap of 54.9% relative to the requirements of modern cloud forensics, with the most pronounced deficiencies in cloud-native structures (−77%), multi-tenancy (−75%), and emerging technologies (−53%). The level of cloud forensics implementation readiness in Indonesia falls within the moderate-to-low range (mean = 2.7/5), with law enforcement agencies facing the most critical obstacles owing to limited resources and an insufficient pool of certified practitioners. Multiple regression analysis (R² = 0.591) identified knowledge level, organizational support, and tools and infrastructure availability as the primary predictors of implementation readiness. Furthermore, a strong expert consensus emerged around the need for chain-of-custody standardization and a national forensic framework as prerequisite conditions for the legal admissibility of cloud-generated digital evidence. This study recommends the development of the Cloud Forensics Framework Indonesia (CFFI)—a hybrid framework integrating the procedural foundations of NIST SP 800-86, the legal provisions of ISO/IEC 27037, cloud-native technical specifications, and applicable national regulations—as the basis for policy reform and the advancement of cloud forensics practice in Indonesia